Pengaruh Beban Kerja dan Dukungan Sosial Terhadap Burnout Pada Karyawan Patotpo Animation Studios (Mansion: Management and Business on Kebangsaan, 2025)
Introduction: The animation industry in Indonesia is growing rapidly, especially with the increasing demand for creative digital content. However, this growth also brings challenges, particularly for employees in animation studios who face high workloads and tight deadlines. Burnout is a common psychological risk that threatens employee well-being and organizational productivity. Background Problems: This study investigates how workload and social support influence burnout among employees at Patopo Animation Studios in Bandung. The central research question is: To what extent do workload and social support affect employee burnout, both partially and simultaneously? Novelty: Although previous studies have discussed the effects of workload and social support on burnout, limited attention has been given to creative industries in Indonesia— especially animation studios, which involve intensive emotional and cognitive labor. This study offers new insights by focusing on this unique organizational context. Research Methods: This research employed a quantitative approach with a saturated sampling technique involving 40 employees. Data were collected using a structured questionnaire and analyzed through multiple linear regression using SPSS 25 to assess partial and simultaneous effects. Finding/Results: The findings reveal that both workload and social support significantly influence burnout, both individually and simultaneously. Workload increases the risk of burnout, whereas social support helps mitigate its effects. The model explains 58.6% of the variance in employee burnout. Conclusion: The study concludes that managing workload and fostering social support are critical in reducing burnout levels in creative work settings. These findings highlight the need for targeted HR policies that balance performance demands with psychological well-being in animation studios.
Keywords: Beban Kerja; Dukungan Sosial; Burnout